The effect of phospholipase A2 from Crotalus durissus collilineatus on Leishmania (Leishmania) amazonensis infection - Passero, Luiz Felipe Domingues [UNESP]; Laurenti, Marcia Dalastra; Tomokane, Thaise Y.; Corbett, Carlos Eduardo P.; Toyama, Marcos H. [UNESP] (Springer, 2008)
In this study, the effect of phospholipase A2 (PLA2) derived from Crotalus durissus collilineatus was evaluated in vitro and in vivo on experimental cutaneous leishmaniasis. The promastigote and amastigote forms treated with PLA2 presented increased growth rate. In vivo studies showed that PLA2-treated Leishmania (Leishmania) amazonensis promastigotes increased the size of lesions in BALB/c mice, and histopathological analysis showed numerous necrotic regions presenting a higher density of polymorphonuclear, mononuclear, and amastigote cells. Additionally, infected macrophages treated with PLA2 were able to generate prostaglandin E2 (PGE2). Cytokine quantification showed that the supernatant from infected macrophages presented moderate and high amounts of IL-2 and IL-10, respectively. However, in PLA2-treated infected macrophages, suppression of IL-2 levels occurred, but not of IL-10 levels. Observation also revealed that both the supernatant and lysate of L. (L.) amazonensis promastigotes exhibited PLA2 activity, which, in the presence of dexamethasone, showed no reduction in their activities; while glucocorticoid maintained the ability of promastigote forms to infect macrophages, which presented values similar to controls. In conclusion, the results indicate that PLA2 may be a progression factor for cutaneous leishmaniasis, since the PLA2 effect suppressed IL-2 levels and generated PGE2, an inflammatory lipid mediator.